2016
DOI: 10.1371/journal.pone.0162505
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnose Links Moonlighting Proteins to Membrane Phospholipid in Mycoplasmas

Abstract: Many proteins that have a primary function as a cytoplasmic protein are known to have the ability to moonlight on the surface of nearly all organisms. An example is the glycolytic enzyme enolase, which can be found on the surface of many types of cells from bacteria to human. Surface enolase is not enzymatic because it is monomeric and oligomerization is required for glycolytic activity. It can bind various molecules and activate plasminogen. Enolase lacks a signal peptide and the mechanism by which it attache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Control of phosphorylation of many of these proteins by the kinase and phosphatase pair PrkC and PrpC is poorly understood at the regulatory level but essential for function (102). However, phosphorylation of M. pneumoniae proteins is widespread even in the absence of PrkC, suggesting the existence of other means by which proteins become phosphorylated (103). Although undiscovered protein kinases may exist, at least some proteins, such as enolase, are labeled with phosphate because of their covalent linkage to phospholipids, representing a recently discovered means by which proteins may be targeted to the plasma membrane.…”
Section: Cytadherencementioning
confidence: 99%
“…Control of phosphorylation of many of these proteins by the kinase and phosphatase pair PrkC and PrpC is poorly understood at the regulatory level but essential for function (102). However, phosphorylation of M. pneumoniae proteins is widespread even in the absence of PrkC, suggesting the existence of other means by which proteins become phosphorylated (103). Although undiscovered protein kinases may exist, at least some proteins, such as enolase, are labeled with phosphate because of their covalent linkage to phospholipids, representing a recently discovered means by which proteins may be targeted to the plasma membrane.…”
Section: Cytadherencementioning
confidence: 99%
“…Such putative secretory routes include the direct translocation of proteins through the cell membrane by dedicated membrane-associated transporters, modulation of the activity of plasma membrane flippases, membrane flipping together with the adhered cytoplasmic proteins exhibiting the affinity for phospholipids and the escape of cytoplasmic proteins during cell division through the fragmentation zone engaging a lock-type mechanism [ 62 , 63 , 64 , 65 , 66 ]. In the case of some human and bacterial moonlighting proteins, it has been suggested that particular post-translational modifications, such as 2-phosphoglycerate-dependent automodification, rhamnosylation or monomethylation, might support their extracellular transport or membrane localization [ 67 , 68 , 69 ]. This issue has yet to be investigated for C. albicans proteins however.…”
Section: Atypical Proteinaceous Components Of Candidal Cell Wallmentioning
confidence: 99%
“…The mechanism of cell surface attachment could potentially be a part of a secretion mechanism, although some recombinantly expressed and purified intracellular/surface moonlighting proteins are capable of reattaching to the cell surface. With a few exceptions [115] most of the ICSPs do not contain known amino acid sequence or structural motifs for attaching to the cell surface. Cell surface attachment could involve a new version of a known mechanism or it may involve an as-yet-unknown mechanism.…”
Section: Secretion Of Intracellular/surface Moonlighting Proteinsmentioning
confidence: 99%